Trajetórias de empregadas domésticas em Feira de Santana (1883-1932) - Santana, Keilane Souza de (2017)
Starting from photos, newspapers, Galdiana Ferreira de Medeiros’ biographical memory, legal proceedings about defloration, rape, bodily injury and homicide crossing I tried reconstruct various maids’ trajectories in the municipality of Feira de Santana between the end of the nineteenth century and the first decades of the twentieth century. Therefore, I started from the premise that these women were disrupted from the civility projects that were born in the Republic because they were poor, black and/or emergent form captivity and often single mothers. The analysis of the sources also allowed to verify that these workers did not always accept submissive their bosses' impositions, assuming various resistance strategies: they can poison them, break away from working relationships and report maltreatments that they experienced in the work environment. Bosses remained to represent them as ungrateful for not accepting the subordination.